2021
DOI: 10.1038/s41598-021-83838-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of a nap following experimental trauma on analogue PTSD symptoms

Abstract: Cognitive models assume that the incomplete integration of a traumatic experience into the autobiographical memory results in typical symptoms associated with post-traumatic stress disorder (PTSD) such as intrusive re-experiencing. Sleep supports the integration of new experiences into existing memory networks through memory consolidation. In fifty-six females, we investigated whether a 90-min daytime nap (n = 33) compared to a wake period (n = 23) after being exposed to an experimental trauma (i.e. a trauma f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Looking at literature published from 2018 and forward only, this is often cited as a fact or as the typical finding. 7,9,16,18,19,21,[24][25][26][27][28][29][30]…”
Section: Introductionmentioning
confidence: 99%
“…Looking at literature published from 2018 and forward only, this is often cited as a fact or as the typical finding. 7,9,16,18,19,21,[24][25][26][27][28][29][30]…”
Section: Introductionmentioning
confidence: 99%
“…One study [17] found higher responses in the sleep group at a retest immediately after the delay interval, but lower responses at a second re-test taking place one week later. One study found no group differences [16], and another study found no effect of pharmacological norepinephrine reduction during sleep on subsequent heart rate responses to emotional stimuli [33]. One study combining participants suffering from PTSD with both trauma-exposed and non-trauma-exposed controls found sleep to decrease responses in several different heart rate-related measures [42].…”
Section: Heart Rate Decelerationmentioning
confidence: 99%
“…This latter effect was however not replicated in a design comparing daytime wake with nighttime sleep [59]. One study found no differences in intrusions or in intrusion distress (after removing two outliers) between a sleep and a sleep deprivation group [60], and one study found no differences in the number of intrusions, intrusion distress, or on scores on the Impact of Event Scale between a nap and wake group [16]. Some studies on this topic have been correlational and observational rather than experimental.…”
Section: Sleep Seems To Make Negative Memories Less Intrusivementioning
confidence: 99%
See 2 more Smart Citations